In vivo evaluation of the effect of sickle cell hemoglobin S, C and therapeutic transfusion on erythrocyte metabolism and cardiorenal dysfunction - D'Alessandro, Angelo; Nouraie, S. Mehdi; Zhang, Yingze; Cendali, Francesca; Gamboni, Fabia; Reisz, Julie A.; Zhang, Xu; Bartsch, Kyle W.; Galbraith, Matthew D.; Gordeuk, Victor R.; Gladwin, Mark T. (American journal of hematology, 2023)
Despite a wealth of exploratory plasma metabolomics studies in sickle cell disease (SCD), no study to date has evaluate a large and well phenotyped cohort to compare the primary erythrocyte metabolome of hemoglobin SS, SC and transfused AA red blood cells (RBCs) in vivo. The current study evaluates the RBC metabolome of 587 subjects with sickle cell sickle cell disease (SCD) from the WALK‐PHaSST clinical cohort. The set includes hemoglobin SS, hemoglobin SC SCD patients, with variable levels of HbA related to RBC transfusion events. Here we explore the modulating effects of genotype, age, sex, severity of hemolysis, and transfusion therapy on sickle RBC metabolism. Results show that RBCs from patients with Hb SS genotypes—compared to AA RBCs from recent transfusion events or SC RBCs—are characterized by significant alterations of RBC acylcarnitines, pyruvate, sphingosine 1‐phosphate, creatinine, kynurenine and urate metabolism. Surprisingly, the RBC metabolism of SC RBCs is dramatically different from SS, with all glycolytic intermediates significantly elevated in SS RBCs, with the exception of pyruvate. This result suggests a metabolic blockade at the ATP‐generating phosphoenolpyruvate to pyruvate step of glycolysis, which is catalyzed by redox‐sensitive pyruvate kinase. Metabolomics, clinical and hematological data were collated in a novel online portal. In conclusion, we identified metabolic signatures of HbS RBCs that correlate with the degree of steady state hemolytic anemia, cardiovascular and renal dysfunction and mortality. D'Alessandro et al. identify red blood cell metabolic markers of hemolysis and cardiorenal dysfunction in 587 sickle cell patients from the WALK PHASST study.